2016
DOI: 10.1155/2016/4310634
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Investigation into Cellular Mechanisms of Cardiac Alternans in Myocardial Ischemia

Abstract: Myocardial ischemia is associated with pathophysiological conditions such as hyperkalemia, acidosis, and hypoxia. These physiological disorders may lead to changes on the functions of ionic channels, which in turn form the basis for cardiac alternans. In this paper, we investigated the roles of hyperkalemia and calcium handling components played in the genesis of alternans in ischemia at the cellular level by using computational simulations. The results show that hyperkalemic reduced cell excitability and dela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…We used it to obtain the Ca 2+ uptake rate per pump and multiplied a scale factor to calculate I up . The appropriate coefficient was determined by comparing the I up amplitude produced by the original ORd epi cell model and the Ca 2+ uptake rate per pump at steady state under normal conditions (this method was described in detail in our previous study [11]). The SERCA pump model incorporates the regulation effect of phospholamban (PLB) on Ca 2+ uptake.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We used it to obtain the Ca 2+ uptake rate per pump and multiplied a scale factor to calculate I up . The appropriate coefficient was determined by comparing the I up amplitude produced by the original ORd epi cell model and the Ca 2+ uptake rate per pump at steady state under normal conditions (this method was described in detail in our previous study [11]). The SERCA pump model incorporates the regulation effect of phospholamban (PLB) on Ca 2+ uptake.…”
Section: Methodsmentioning
confidence: 99%
“…The link between ischemia and alternans has been extensively explored [10]. Our previous simulations identified that hyperkalaemia, one component of ischemia, results in depolarization alternans [11]. Other two ischemic components, hypoxia and acidosis, lead to repolarization alternans by causing instabilities in calcium cycling [4, 11, 12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies [2,6] point out the important effect of I CaL on blocks, but yet they don ' t explain how it associates with conduction delay under hyperkalaemic conditions. In addition, I CaL plays an important role in alternans occurring in the single cell under hyperkalaemic conditions [14].…”
Section: Discussionmentioning
confidence: 99%